2009
DOI: 10.1093/rheumatology/ken504
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinimetric properties of the Early Inflammatory Arthritis--self-administered comorbidity questionnaire

Abstract: The EIA-SCQ is reliable and valid for use in EIA. It has the potential to become a useful measure of comorbidity in outcome studies of EIA when the resources for a full medical chart review are unavailable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It is well recognized that the experienced functional limitations due to AS are partly influenced by disease activity [35], explaining the weak correlation between the SCQ and AS-related disease activity when keeping the rheumatic items and its impact on function into the questionnaire. The adequate construct validity of the mSCQ found in de present study is consistent with a previous study evaluating an adapted version of the SCQ in patients with early inflammatory arthritis [20]. A study in patients with SLE and SSc, however, showed that these patients could not distinguish comorbidities from their index disease, which confirms the importance of removing comorbidities with overlapping symptoms with the index disease from the questionnaire [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is well recognized that the experienced functional limitations due to AS are partly influenced by disease activity [35], explaining the weak correlation between the SCQ and AS-related disease activity when keeping the rheumatic items and its impact on function into the questionnaire. The adequate construct validity of the mSCQ found in de present study is consistent with a previous study evaluating an adapted version of the SCQ in patients with early inflammatory arthritis [20]. A study in patients with SLE and SSc, however, showed that these patients could not distinguish comorbidities from their index disease, which confirms the importance of removing comorbidities with overlapping symptoms with the index disease from the questionnaire [21].…”
Section: Discussionsupporting
confidence: 91%
“…The SCQ was validated in 170 inpatients from medical and surgical care units and was found to be an efficient instrument to assess comorbid conditions in clinical and health services research among patients with a broad range of the underlying diseases [19]. The clinimetric properties of the SCQ have also been validated in some rheumatic diseases [20,21]. In AS, the SCQ has been used as an instrument to measure comorbidity [2], but aspects of validity have never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…While the SCQ survey has been validated, with good test-retest reliability being reported [23,42], this is the first time that it has been examined in a prostate cancer population. This is despite the fact that it has been recommended by ICHOM as the preferred method for collecting comorbidities in men with localised prostate cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…Participants recruited to the McGill Early Arthritis Registry participated in this study [25]. The inclusion criteria were as previously described and included one or more joints inflamed >6 weeks, but <12 months.…”
Section: Patientsmentioning
confidence: 99%